Optic pathway and hypothalamic glioma, old problems, new paradigms - Inci Yaman Bajin; Eric Bouffet (Elsevier, 2023)
Optic pathway/hypothalamic gliomas (OP/HGs) are low-grade tumours that account for 3-5% of all pediatric CNS tumours. The majority of cases are diagnosed before the age of 20, and 75% before the age of 10 years. Presenting symptoms are essentially visual. Treatment is recommended when the tumour threatens the patient's vision. Even though they are low-grade tumours, their course can be unpredictable and their management is often challenging. As OP/HGs are generally not amenable to complete resection, surgery has a limited role in the management. Chemotherapy was essentially the treatment of choice in the past but in most series, the 5-year event-free survival was between 30 and 50%. Targeted therapies are starting to gain ground over recent years with a better understanding of the underlying molecular alterations.